2019
DOI: 10.1200/po.18.00271
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Survival Analysis of Patients With Resected Pancreatic Ductal Adenocarcinoma and a Germline BRCA or PALB2 Mutation

Abstract: PURPOSE Germline mutations in the homologous recombination genes BRCA1, BRCA2, and PALB2 confer an increased risk for pancreatic ductal adenocarcinoma (PDAC). Tumors associated with mutations in homologous recombination genes are sensitive to DNA-damaging agents. We retrospectively studied patients with resected PDAC and a pathogenic germline mutation in one of these three genes. The planned analyses included overall survival (OS) and changes therein when platinum chemotherapy was used in the perioperative set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 15 publications
3
28
0
Order By: Relevance
“…Response duration was also significantly longer compared to what has been reported, likely secondary to increased sensitivity to DNA-damaging drugs. The increased survival is comparable to previous research on DDR-related pancreatic cancer cohorts 3,12 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Response duration was also significantly longer compared to what has been reported, likely secondary to increased sensitivity to DNA-damaging drugs. The increased survival is comparable to previous research on DDR-related pancreatic cancer cohorts 3,12 .…”
Section: Discussionsupporting
confidence: 85%
“…Another study reported median time of survival of 11 months in the BRCA1/2-population (95% CI, 1.5-12) and 23.3 months in BRCA1/2+ group (95% CI, 3.8-30.2) with cisplatin, gemcitabine and veliparib 3 . Others found median survival was 46.6 months for those with a pathogenic BRCA1/2 or PALB2 variant following platinum exposure compared to 23.3 for those without a variant detected 12 .…”
Section: Introductionmentioning
confidence: 99%
“…56 Finally, Yu et al (2018) reported a trend towards improved median OS with neoadjuvant platinum-based therapy in patients with resectable PDAC and pathogenic germline mutations in BRCA1/2 or PALB2 as compared to patients without pathogenic germline mutations (not met vs 23.1 months, p=0.07). 57 In a prospective Phase IB/II trial, Jameson et al (2019) studied gemcitabine, nab-paclitaxel, and cisplatin in an unselected cohort of 25 patients that included three patients with BRCA2, two with ATM and one with RAD51. 58 The median OS of the three patients harboring BRCA2 ranged from 39.8 to 45.3 months and all three patients experienced a partial radiographic response.…”
Section: Therapeutic Approaches Dna Damaging Agentsmentioning
confidence: 99%
“…85 PALB2 is currently considered an equivalent HRD biomarker to BRCA1/2 germline alterations. 54,56,57,59 Whether other germline mutations in the HRD pathway are equivalent HRD biomarkers to BRCA1/2 remains unknown. Germline mutations in PALB2, ATM, CHEK2 are currently being investigated in clinical studies testing PARP inhibitors (Table 3).…”
Section: Non-germline Brca Biomarkers Non-brca Germline Mutationsmentioning
confidence: 99%
“…Another study reported median time of survival of 11 months in the BRCA1/2-population (95% CI, 1.5-12) and 23.3 months in BRCA1/2+ group (95% CI, 3.8-30.2) with cisplatin, gemcitabine and veliparib [2]. Others found median survival was 46.6 months for those with a pathogenic BRCA1/2 or PALB2 variant following platinum exposure compared to 23.3 for those without a variant detected [12].…”
Section: Introductionmentioning
confidence: 99%